Obesity is associated with worse oncological outcomes in patients treated with radical cystectomy. (21st June 2012) - Chromecki, Thomas F.; Cha, Eugene K.; Fajkovic, Harun; Rink, Michael; Ehdaie, Behfar; Svatek, Robert S.; Karakiewicz, Pierre I.; Lotan, Yair; Tilki, Derya; Bastian, Patrick J.; Daneshmand, Siamak; Kassouf, Wassim; et al.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Little is known on the association between obesity and urothelial carcinoma of the bladder (UCB). Most studies have shown that higher body mass index (BMI) is associated with higher rates of perioperative complications. Only one study specifically investigated obesity and bladder cancer‐specific outcomes and reported no significant association between higher BMI and disease‐specific survival in patients with UCB treated with radical cystectomy. However, that study was limited by its small sample size and a high rate of preoperative therapies. In contrast to the only previous study evaluating the association of BMI with oncological outcomes in UCB, we found that obesity (BMI ≥30 kg/m2) was associated with features of biologically aggressive UCB and clinical outcomes after radical cystectomy and, even when adjusting for the effects of standard clinicopathological features, obesity remained an independent predictor of cancer recurrence, cancer‐specific mortality and overall mortality. Objective To investigate the association between body mass index (BMI) and oncological outcomes in patients after radical cystectomy (RC) for urothelial carcinoma of the bladder (UCB) in a large multi‐institutional series. Patients and Methods Data were collected from 4118 patients treated with RC and pelvic lymphadenectomy for UCB. Patients receiving preoperative chemotherapy or radiotherapy were excluded. Univariable and multivariable models tested the effect of BMI on disease recurrence, cancer‐specific mortality and overall mortality. BMI was analysed as a continuous and categorical variable (<25 vs 25–29 vs ≥30 kg/m2). Results Median BMI was 28.8 kg/m2 (interquartile range 7.9); 25.3% had a BMI <25 kg/m2, 32.5% had a BMI between 25 and 29.9 kg/m2, and 42.2% had a BMI ≥30 kg/m2. Patients with a higher BMI were older (P < 0.001), had higher tumour grade (P < 0.001), and were more likely to have positive soft tissue surgical margins (P = 0.006) compared with patients with lower BMI. In multivariable analyses that adjusted for the effects of standard clinicopathological features, BMI >30 was associated with higher risk of disease recurrence (hazard ratio (HR) 1.67, 95% confidence interval (CI) 1.46–1.91, P < 0.001), cancer‐specific mortality (HR 1.43, 95% CI 1.24–1.66, P < 0.001), and overall mortality (HR 1.81, CI 1.60–2.05, P < 0.001). Themain limitation is the retrospective design of the study. Conclusions Obesity is associated with worse cancer‐specific outcomes in patients treated with RC for UCB. Focusing on patient‐modifiable factors such as BMI may have significant individual and public health implications in patients with invasive UCB.